2021
DOI: 10.3847/1538-4357/abeab2
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation Timescales of the Halo Populations from Asteroseismology and Chemical Abundances*

Abstract: We combine asteroseismology, optical high-resolution spectroscopy, and kinematic analysis for 26 halo red giant branch stars in the Kepler field in the range of −2.5 < [Fe/H] < −0.6. After applying theoretically motivated corrections to the seismic scaling relations, we obtain an average mass of 0.97 ± 0.03 M ⊙ for our sample of halo stars. Although this maps into an age of ∼7 Gyr, significantly younger than independent age estimates of the Milky Way stellar halo, we considered this app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 194 publications
(285 reference statements)
8
24
0
Order By: Relevance
“…Cu: We find depleted [Cu/Fe] abundances for the blob stars with mean of −0.35 dex, where the trend is essentially flat for [Fe/H] > −1.5 dex but is decreasing with decreasing [Fe/H] below this value. Our Cu result agrees with that of Nissen & Schuster ( 2011 ) as well as the more recent study from Matsuno et al ( 2020 ), where both show [Cu/Fe] abundances below 0 dex for low-α accreted halo stars. Taking into account the difference between our solar Cu abundance and that of Asplund et al ( 2009 ) (Reddy et al 2003(Reddy et al , 2006Yong et al 2013 ;Bensby 2014 ;Battistini & Bensby 2015 ), gold pentagons for accreted stars (Nissen & Schuster 2010, 2011Fishlock et al 2017 ), and green triangles for LMC (Van der Swaelmen et al 2013 ).…”
Section: Light and Odd-z Elementssupporting
confidence: 92%
See 2 more Smart Citations
“…Cu: We find depleted [Cu/Fe] abundances for the blob stars with mean of −0.35 dex, where the trend is essentially flat for [Fe/H] > −1.5 dex but is decreasing with decreasing [Fe/H] below this value. Our Cu result agrees with that of Nissen & Schuster ( 2011 ) as well as the more recent study from Matsuno et al ( 2020 ), where both show [Cu/Fe] abundances below 0 dex for low-α accreted halo stars. Taking into account the difference between our solar Cu abundance and that of Asplund et al ( 2009 ) (Reddy et al 2003(Reddy et al , 2006Yong et al 2013 ;Bensby 2014 ;Battistini & Bensby 2015 ), gold pentagons for accreted stars (Nissen & Schuster 2010, 2011Fishlock et al 2017 ), and green triangles for LMC (Van der Swaelmen et al 2013 ).…”
Section: Light and Odd-z Elementssupporting
confidence: 92%
“…More recent studies (e.g. Matsuno et al 2020Matsuno et al , 2021Aguado et al 2021 ) also find r-process enhancement in GES stars. Most of the studies aforementioned have samples of 10-30 low-α stars, but as been shown with more recent studies using large surv e ys (e.g.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The mean age of GSE stars is found to be ≈ 10 Gyr (e.g. Kilic et al 2019;Borre et al 2021;Montalbán et al 2021;Matsuno et al 2021b). On the other hand, Sequoia stars are found to be slightly older than GSE (e.g.…”
Section: Sequoia and Other Very Retrograde Substructuresmentioning
confidence: 99%
“…In the present study we compare Eu abundances of stars in Gaia-Enceladus with those of stars formed in the Milky Way (the in situ stars having high-[Mg/Fe]) with the aim of obtaining constraints on r-process enrichment processes. Although Ishigaki et al (2013), Fishlock et al (2017), andMatsuno et al (2021) presented hints of Eu enhancements of the low-Mg halo stars, their samples were of limited size. Thanks to the Gaia mission and the recent data release from the optical high-resolution spectroscopic survey, the Galactic Archaeology with HERMES (GALAH; De Silva et al 2015), we can now study this phenomenon with a larger sample analysed homogeneously.…”
Section: Introductionmentioning
confidence: 98%